Penerapan Latihan Berkenalan untuk Meningkatkan Kemampuan Sosialisasi pada Pasien Skizofrenia dengan Isolasi Sosial: Systematic Literature Review - Lia Rahmawati; Endah Sari Purbaningsih; Erida Fadila (CV. ALIM'SPUBLISHING, 2026)
Social isolation is one of the most common nursing problems found in schizophrenia patients. This condition is characterized by withdrawal from social interactions, decreased communication ability, and barriers in building meaningful interpersonal relationships. Without proper and structured nursing interventions, social isolation has the potential to worsen the prognosis of mental illness and significantly reduce the patient's quality of life. Introduction training as one of the implementation strategies in psychiatric nursing is believed to be capable of improving patients' socialization ability gradually and measurably. This literature review aims to systematically analyze the effectiveness of introduction training in improving socialization ability in patients with social isolation, including its impact on verbal and nonverbal communication, social function, and its comparison with other psychosocial interventions. This study uses the Systematic Literature Review (SLR) method based on the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Literature searches were conducted on five electronic databases, namely PubMed, ScienceDirect, Google Scholar, ProQuest, and Sage Journals, with a publication time range of 2020 to 2026. From a total of 312 identified articles, 20 articles ultimately met the inclusion criteria and were analyzed in depth. The results of the analysis show that introduction training is consistently proven effective in improving the socialization ability of patients with social isolation. This intervention is able to improve verbal and nonverbal communication skills, improve eye contact, encourage the initiation of social interaction, and increase participation in group activities. Introduction training is recommended to be systematically integrated into the standard of psychiatric nursing care in hospitals and communities.